The Influence of Service Quality and Trust on Customer Satisfaction in Catering Mbak Daeng Alauddin Tangerang District - Pujangga, Akbar Maulana; Pratama, Edo; Kesumawati, Christien Setiya; Al amri, Amaliya Nor (Jurnal Indonesia Sosial Sains, 2024)
Service quality and trust are two major factors determining customer satisfaction, especially in service industries such as catering. Understanding the influence of these two factors is important to improve competitiveness and maintain customer loyalty. This study aims to determine the influence of service quality and trust on partial or simultaneous consumer satisfaction in catering Mbak Daeng Alauddin, Tangerang Regency. The research methods used are descriptive and associative. The population in this study is 350 consumers. The sampling technique with the probability sampling method is proportionate stratified random sampling using the 10% Slovin formula. The sample was obtained as many as 78 respondents. The data analysis method used is multiple regression analysis. The results of the study partially show that the quality of service has a positive and significant effect on customer satisfaction, which can be concluded from the t-count value > t-table (8.932 > 1.99167), the trust has a positive and significant effect on consumer satisfaction, it can be concluded that the t-count value > t-table (6.668 > 1.99167), by simultaneously showing that service quality and trust simultaneously have a positive and significant effect on customer satisfaction can be It was concluded that the value of F-calculated > F-table (48.663 > 2.37).